Analysis of the Implementation of E-Purchasing for Construction Services on Efficiency and Transparency in the Bina Marga Division of the Public Works and Spatial Planning Department (PUP) - Rika Yuanita; Bambang Endro Yuwono (Eduvest - Journal of Universal Studies, 2026)
Government procurement of goods and services is driven towards efficient, transparent, and accountable governance through digitalization, one of which is with an e-catalog-based e-purchasing system developed by LKPP to standardize and document transactions electronically. Analyze the implementation of e-purchasing construction services on the efficiency and transparency of procurement in the Highway Division of the PUPR Office of the Bangka Belitung Islands Province, including the effectiveness of its implementation, benefits, and implementation constraints. Analysis of the implementation of e-purchasing construction services by reviewing the effectiveness of the system, the benefits produced, and the obstacles in implementation practice. E-purchasing speeds up the procurement process, increases the disclosure of price and specification information, and reduces the potential for non-transparent practices. However, there are obstacles in the form of limited human resource competence, incompatibility with e-catalog specifications with field conditions, and not optimal updating of provider data. E-purchasing contributes to the efficiency and transparency of the procurement of construction services, but requires strengthening managerial, technical, and supervisory aspects so that its implementation is more optimal and sustainable.